Rancang Bangun Sistem Pemadam Kebakaran Box Panel Outdoor Menggunakan Arduino Uno Berbasis GSM SIM800L V1 - Lanina Milenise Fisabili; Tri Wahyu Oktaviana Putri (Sekolah Tinggi Teknik - PLN, 2021)
With the installation of electrical installations on the panel box, there is a risk of interference causing fires caused by electricity due to short circuits, burning cables due to poor insulators and MCBs being burned due to overload. So we need a fire extinguishing system on the panel box that can minimize the risk of a large fire and can be monitored remotely. The extinguishing system consists of Arduino Uno as a microcontroller to process data, Infrared sensor KY-026 and temperature sensor DS18B20 as input to detect fire and excess temperature in the box panel. The MG995 Servo Motor and buzzer are used as outputs for the APAR drive and provide early warning. GSM SIM800L V1 as a remote communication to provide notifications to cell phones when fires and excessive temperatures occur. The test results in this study is a fire extinguishing system with KY-026 Infrared sensor which is able to detect fire at an angle of 60°. The DS18B20 temperature sensor detects a temperature of 41°C indicating overheating, as well as the MG995 Servo Motor rotates 90° and the buzzer sounds an alarm then the GSM SIM800L V1 sends a notification remotely which is 1210 meters or even more.